2009
DOI: 10.1037/a0017022
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in complex addition: Efficient Chinese versus adaptive Belgians and Canadians.

Abstract: In the present study, the authors tested the effects of working-memory load on math problem solving in 3 different cultures: Flemish-speaking Belgians, English-speaking Canadians, and Chinese-speaking Chinese currently living in Canada. Participants solved complex addition problems (e.g., 58 ϩ 76) in no-load and working-memory load conditions, in which either the central executive or the phonological loop was loaded. The authors used the choice/no-choice method to obtain unbiased measures of strategy selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 71 publications
(104 reference statements)
9
53
0
Order By: Relevance
“…An analysis of French Kit scores confirmed that the Chinese had a substantially higher level of arithmetic skill than did the Canadians [54 vs. 34; F(1,61) cant decrements in solution times in the dual-task conditions. In accord with previous findings about cultural differences, Chinese participants performed better on the subtraction problems than did the Canadian participants: They solved the problems more quickly and more accurately and were less affected by problem complexity (Campbell & Xue, 2001;Imbo & LeFev re, 2009). However, only the Chinese participants showed differential decrements related to presentation format (cf.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…An analysis of French Kit scores confirmed that the Chinese had a substantially higher level of arithmetic skill than did the Canadians [54 vs. 34; F(1,61) cant decrements in solution times in the dual-task conditions. In accord with previous findings about cultural differences, Chinese participants performed better on the subtraction problems than did the Canadian participants: They solved the problems more quickly and more accurately and were less affected by problem complexity (Campbell & Xue, 2001;Imbo & LeFev re, 2009). However, only the Chinese participants showed differential decrements related to presentation format (cf.…”
Section: Resultssupporting
confidence: 75%
“…Both studies tested only complex addition, however, so the present study extends these results to other operations by showing that Canadians need both phonological and visual working memory resources when performing complex subtraction and multiplication. Given the higher level of mathematical skill in Asian than in Canadian participants (Campbell & Xue, 2001;Imbo & LeFev re, 2009;LeFev re & Liu, 1997;Siegler & Mu, 2008), we had anticipated that working memory load effects might be less in the Chinese than in the Canadian participants. However, Chinese-educated participants in the present research did slow down under phonological and visual working memory loads, even though other Chinese participants did not rely on executive working memory resources when solving complex addition problems (Imbo & LeFev re, 2009).…”
Section: Secondary Task Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as in previous research with Chinese-educated participants, the Chinese participants' computational skill was much superior to that of other groups (Campbell & Xue, 2001;LeFevre & Liu, 1997;Imbo & LeFevre, 2009.…”
Section: Methods Participantssupporting
confidence: 52%
“…Imbo and LeFevre (2009) defined adaptivity as the percentage of trials on which participants chose the fastest strategy as determined by their personal efficiency performance. This type of adaptivity is person based because it is relative to CULTURAL DIFFERENCES IN COMPUTATIONAL ESTIMATION 4 an individual's performance.…”
mentioning
confidence: 99%